Slime mold inspired swarm robot system for underwater wireless data communication - Vicerra, Ryan Rhay P. (Animo Repository, 2016)
Swarm robotics is a collection of mobile robots that displays swarm behavior. This paper presents a simulator of slime mold amoeba inspired swarm robot for underwater wireless communication system. The slimemold inspired robotic swarm is used to overcome the challenges of transmitting data in a large underwater environment. Underwater communication systems today are primarily acoustic technology and characterized by limited and distance dependent bandwidth, presence of multipath, and low speed of sound propagation. The robots navigate and seek the shortest path creating a virtual connection between the data transmitter and receiver similar to the foraging behavior of swarms. Each individual robot going back and forth from the transmitter to the receiver and vice-versa acts as a "physical" carrier of the data. Swarm robots navigate using swarmlevel intelligence based on the signal propagation technique used by slime mold amoeba aggregation using acoustics communication. The robot swarm system is developed, simulated and tested using the coded simulator. Using the slime mold inspired swarm robot system; the simulation successfully performed the data "foraging" scenario and showed the ability of the swarm to provide a virtual link in an underwater wireless communication network.